2009
DOI: 10.5650/jos.58.91
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sterol Lipids in Kluyveromyces lactis Strain M-16 Accumulating a High Amount of Steryl Glucoside

Abstract: Kluyveromyces lactis strain M-16 isolated from raw milk accumulates a high amount of steryl glucoside in the cells. Under high temperature or in the presence of NaCl, this strain did not show better growth than other K. lactis strains that hardly accumulated steryl glucoside. Heat shock elevated the content of steryl glucoside 3.2-fold, which accounted for 27% of the total sterol lipids, and simultaneously reduced that of acyl sterol. Both strains, M-16 and NBRC 1267, contained ergosterol as a principal compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, the physiological relevance of this increase is still unclear. For instance, in yeasts, certain strains of Kluyveromyces lactis usually do not produce detectable amounts of SGs, except strain M-16, isolated from raw milk and milk products, in which the level of SGs (mostly made by ergosterol and dihydroergosterol) is surprisingly high, reaching 27% of the total sterol-derived lipids [33]. Because neither ergosterol nor dihydroergosterol are present in milk, these SGs are synthesized by K. lactis M-16.…”
Section: Sterylglucosides In Fungimentioning
confidence: 99%
“…However, the physiological relevance of this increase is still unclear. For instance, in yeasts, certain strains of Kluyveromyces lactis usually do not produce detectable amounts of SGs, except strain M-16, isolated from raw milk and milk products, in which the level of SGs (mostly made by ergosterol and dihydroergosterol) is surprisingly high, reaching 27% of the total sterol-derived lipids [33]. Because neither ergosterol nor dihydroergosterol are present in milk, these SGs are synthesized by K. lactis M-16.…”
Section: Sterylglucosides In Fungimentioning
confidence: 99%
“…Finally, much of this research came to fruition due to the first identification, description, and cloning of the steryl glycosyltransferase (SGT) and sterylglucosidase (Sgl) enzymes in fungi. Both SGT and Sgl enzymes were described in plants, fungi, yeast, and more recently bacteria, humans, and rodents [1,8,11,15,33,44,46,61,[64][65][66][67]. Warnecke and colleagues [64] described the first SGT enzymes in the fungi S. cerevisiae gene UGT51, C. albicans gene UGT51C1, Pichia pastoris gene UGT51B1, and Dictyostelium discoideum gene UGT52 using amino acid sequence similarities from a previously identified SGT enzyme (Ugt80A1, Ugt80A2) in plants, and cloned these enzymes for in vitro activity [68,69].…”
Section: Steryl Glycosides and Other Conjugated Sterolsmentioning
confidence: 99%
“…Although SGs were shown in several examples to boost response to stress, not all SGs are made equally. One study investing the sterol contents of two Kluyveromyces strains found that Kluyveromyces lactis strain M-16 that produces high amounts of SGs did not have any growth advantage under high temperatures or in the presence of high concentrations of NaCl compared to K. lactis strain NBRC 1267 that does not naturally produce SGs [66]. The Kluyveromyces strains are phylogenetically similar to both Saccharomyces cerevisiae and Candida albicans, which have all been shown to produce and respond differently to SG production, even though ergosterol is the major sterol source in all of these fungi.…”
Section: Fungimentioning
confidence: 99%